2013
DOI: 10.3390/molecules18021949
|View full text |Cite
|
Sign up to set email alerts
|

Euphorbia formosana Root Extract Induces Apoptosis by Caspase-Dependent Cell Death via Fas and Mitochondrial Pathway in THP-1 Human Leukemic Cells

Abstract: Acute myeloid leukemia (AML), a very rare type of cancer, generally affects patients over 50 years old. While clinical drugs to treat advanced stages of AML exist, the disease becomes increasingly resistant to therapies. Euphorbia formosana Hayata (EF) is a native Taiwanese medicinal plant used to treat rheumatism, liver cirrhosis, herpes zoster, scabies, and photoaging, along with tumor suppression. However, the mechanisms by OPEN ACCESSMolecules 2013, 18 1950 which it suppresses tumors have not been explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…Mitochondria play a central role in apoptosis. Several studies have shown that toxin and natural products could induce leukemia cell apoptosis through the mitochondrial pathway (Hsieh et al, 2013;Lee et al, 2005;Salim et al, 2013;Zhang et al, 2012). The results presented in this study also indicate that the mitochondrial pathway is involved in the apoptotic process induced by LukS-PV in HL-60 cells.…”
Section: Discussionsupporting
confidence: 71%
“…Mitochondria play a central role in apoptosis. Several studies have shown that toxin and natural products could induce leukemia cell apoptosis through the mitochondrial pathway (Hsieh et al, 2013;Lee et al, 2005;Salim et al, 2013;Zhang et al, 2012). The results presented in this study also indicate that the mitochondrial pathway is involved in the apoptotic process induced by LukS-PV in HL-60 cells.…”
Section: Discussionsupporting
confidence: 71%
“…This effect has been observed for the hexane extract of the latex from E. umbellata and other matrices obtained from Euphorbia species, against leukemia cell lineages. [10,12,14,25,26] The cell cycle analysis demonstrated that the treatment with Dcm increased S and G2/M population (compared with the negative control), as observed to doxorubicin ( Figure 4). Similar data already demonstrated the same effect of doxorubicin in HL-60 cell and some lymphoma cell line cycle, showing an increase of S and G2/M phase cell population, which appears to be related with the upregulation of cyclin B1 and cyclin A2, and expression of topoisomerase IIα.…”
Section: Cytotoxic Assaymentioning
confidence: 70%
“…Extracts from plants and their secondary metabolites particularly alkaloids, polyphenolics and terpenoids exhibit anticancer activity by the inhibition of cell proliferation, blocking cell cycle and increasing apoptosis in cancer cells . The plants are inexpensive, easily available and low or absolutely non‐toxic in cancer therapy . Rhaponticum carthamoides (Willd.)…”
Section: Introductionmentioning
confidence: 99%